Caracterização multidimensional da dor lombar em idosos: dados do estudo Back Complaints in the Elders BACE Project - Fabianna Resende de Jesus Moraleida (2016)
Low back pain (LBP) is the most disabling health condition worldwide. According to the Global Burden of Disease Study (GBD), which has developed an indicator called DALY (Disability Adjusted Life Years), LBP has its peak prevalence during the sixth decade of life. However, there are few studies that explore LBP in older adults according to the biopsychosocial approach advocated by LBP literature. Moreover, as most of the epidemiological studies on LBP were conducted with adults, many findings about the condition in the literature do not present relevant information in the geriatric and gerontology perspective, thus making it difficult to understand the magnitude of its impact on older people who have it. Within this context, researchers from Brazil, Australia and the Netherlands established the Back Complaints in the Elders (BACE) consortium. This is an epidemiological observational and longitudinal research that was designed to determine the duration, severity and clinical course of back pain in older adults with a new episode of this complaint, and to identify prognostic factors for chronicity in this population. This thesis had the main objective to analyze multidimensional aspects of back pain in Brazilian and Dutch older adults from the international consortium BACE. Five articles resulting from the research conducted in the thesis were produced. Article 1 describes the profile of the Brazilian older adults from Brazilian BACE considering socio-demographic and clinical data, behavioral factors, lifestyle, and physical / functional conditions associated with LBP. Also, this article considered subgroups of participants of different ages, economic levels and education in the analysis. According to this, people aged 75 years or older had slightly lower levels of disability (mean difference in Roland Morris Disability Questionnaire of 1,29, 95% confidence interval, CI: 0,03 to 5,56), perceived having better quality of life in Sf-36 physical component, had greater self- efficacy for falls on Falls Efficacy Scale International (mean difference 2,41, 95% CI 0,35 to 4,46), lower walking speed, as compared to the younger age group. The comparison between groups of education and income levels revealed that participants with income equal to or less than two minimum wages had higher disability (p = 0,01), more pain catastrophizing (p = 0,01) and took longer to perform the Timed Up and Go test (p = 0,04), compared to those with higher income. Participants with four or fewer years of schooling also had worse performance in these variables and additionally reported greater intensity of leg pain (p <0,001) and in the lower back (p = 0,03). Article 2 identified an association between the variables physical activity levels and disability in elderly Brazilians with LBP, and showed that depressive symptoms partially mediated this association. Physical activity level, assessed by the reduced version of the International Physical Activity Questionnaire, disability by the Roland Morris Disability Questionnaire, and depressive symptoms by the Center of Epidemiologic Studies in Depression. Being physical activity inversely proportional to disability (B = -1,65, 95% Confidence Interval-CI of -2,32 to -0,99), there was an indirect effect of PA in reducing disability through lower levels of depressive symptoms. In this case, having lower depressive symptoms was associated with having lower levels of disability. To compare the baseline characteristics of Brazilian and Dutch older adults with a new episode of back pain, and investigate whether socio-demographic characteristics and lifestyle are associated with pain and disability, Article 3 used information from 602 Brazilian and 675 Dutch with 66.7 and 66.4 years old, respectively, who participated in BACE consortium. Analyzes were conducted between countries to compare characteristics of the participants, and to investigate associations between socio-demographic characteristics and lifestyle, and intensity of pain and disability. Results showed that samples differed significantly in their overall characteristics. Brazilian participants showed greater intensity of pain (mean difference 2,01; 95% CI = 1,20 to 2,31) and disability (mean difference 3,95, 95% CI = 3,29 to 4,2). Additionally, the major differences for psychological distress were observed for depressive symptoms (average of 8,52 difference; 95% CI = 7,39 to 9,66), and pain catastrophizing (mean difference 7,77, 95% CI = 6,0 to 9,14), with worst reports coming from Brazilian participants. There was no difference between groups for the performance in the Timed Up and Go test. By controlling the effect of the country, being female and having altered quality of sleep were associated with higher pain intensity. Also, having altered quality of sleep, having two or more comorbidities, and being physical inactive were associated with greater perceived disability. Being more educated was negatively associated with pain and disability. Data analysis from studies that were implemented in Brazil, United Stated and the Netherlands shown in Article 4 demonstrated that opioids were being used in clinical practice by older adults with back pain. Interesting, 25% of older adults from the United States had registries on opioids when considering the timeframe from baseline up to three months of follow-up. Although Brazilian and Dutch older adults were also using this medication, their frequencies were smaller. Patients with opioids registries had more back and leg pain at baseline, reported worse perceived quality of life, and more of them had depressive symptoms. Finally, Article 5 was the development of a protocol for a systematic review to investigate the effects of exercise for pain, disability related to pain and physical / functional capacity in elderly patients with LBP. This protocol pointed out the importance of the studying therapeutic exercises by looking through the aging perspective. The Cochrane Database of Systematic Reviews published the protocol in April 2016.